Diseño de un plan de mejoramiento integral para la reducción de costos e impacto ambiental generdos por la devolución y destrucción de productos, comercializados por el centro de distribución de productos Avon Ecuador S.A. ubicado en el sector de Amaguaña - Salvador Caicedo, Tania Elizabeth (2015)
The present investigation work realized in Productos Avon Ecuador S.A. has as principal objective to design an improvement plan through an Administrative-Operative information system, based on bringing up processes and the subsequent measurement of the time and costs generated in each of the activities, identifying unfavorable aspects in daily operation, and with it establish strategies to improve the performance of the associates, the effectiveness of their processes and service quality, minimizing the return of products and their consecuences en terms of money and environmental impact. Details the theoretical support for the management systems, based on the focus on processes and environment as well as terms and concepts that cover the improvement plan and criterias that are involved in the operation of the company. Describes the historical review of the company, the commercial activity and propounds its internal and external analysis, its SWOT matrix, and the survey, which would allow us to know its current situation, the problematic and deficiencies within the department and its work environment. Proposes a new model of management based on characterization tabs with focus on processes, details the proposal of improvement based on the strategic plan of the department, improvement of the processes, decrease of devolutions and the implementation of the management model. Finally the conclusions and general recommendations are put forth based on the study carried out.